(untitled) (Asian Journal of Medical and Biological Research, 2025)
Anemia remains one of the most widespread nutritional disorders globally and poses a substantial public health challenge, particularly among pregnant women in low- and middle-income countries. During pregnancy, the body’s demand for iron increases to support fetal growth and maternal blood volume expansion; failure to meet this demand often results in maternal anemia, adversely affecting both maternal and neonatal outcomes. This study aimed to assess the prevalence of anemia among illiterate pregnant women in Bangladesh and examine its association with educational, socioeconomic, and dietary factors. A cross-sectional study was conducted at the Maternal and Child Health Training Institute (MCHTI), where 100 randomly selected pregnant women receiving antenatal care (ANC) participated. Data were analyzed using descriptive statistics, and chi-square tests were applied to identify associations between anemia and socioeconomic variables. The overall prevalence of anemia was 71%, with significantly higher rates among illiterate women (95.84%) compared to literate women (48.1%). Among illiterate pregnant women, mild anemia was found in 60.4%, moderate anemia in 27.1%, and severe anemia in 8.3% of cases. Anemia was more prevalent (65.22%) during the second trimester, and 89.58% of illiterate women came from low-income families. The findings suggest that insufficient education, limited dietary diversity, inadequate medical examinations, and insufficient iron supplementation contribute to the elevated prevalence of anemia. The study concludes that anemia remains a serious public health issue among pregnant women in Bangladesh. The findings imply that improving educational attainment, promoting nutrition awareness, and providing socioeconomic and antenatal support are essential to reducing anemia and improving maternal and fetal health outcomes. Asian J. Med. Biol. Res. 2025, 11(4), 125-134